An in-situ study in the Xijiang River basin revealed adverse effects of total dissolved gas supersaturation on fish - Xuefeng Chen; Zhiguang Zhang; Yunong Qin; Shikang Liu; Yuanming Wang; Jingjie Feng; Kefeng Li (Ecotoxicology and Environmental Safety)
High dam discharge can lead to total dissolved gas (TDG) supersaturation in downstream rivers, causing fish to suffer from bubble trauma and even mortality. Focusing on the Datengxia hydropower station in the Xijiang River basin, we conducted in-situ experiments to explore the tolerance patterns of economic fish species, including Ctenopharyngodon idella, Hypophthalmichthys molitrix, and Cirrhinus molitorella, under the influence of TDG supersaturation at different compensation depths. Moreover, the development and recovery patterns of bubble trauma and the swimming ability of fish exposed to TDG supersaturated water were investigated. In-situ experiments showed that TDG supersaturation ranged from 112.2 % to 125.2 %, averaging 118.3 % at the experiment site. The results revealed that compensation depth is favorable in fish avoidance of TDG supersaturation. The survival rate of the experimental fish at the surface was lower than for those at the 0–3 m water depth. The survival rates of Ctenopharyngodon idella, Hypophthalmichthys molitrix, and Cirrhinus molitorella at the surface were only 30 %, 47.5 %, and 70 %, respectively, while at the 0–3 m water depth, the survival rates were 97.5 %, 87.5 %, and 87.5 %, respectively. Additionally, the survival rate of fish was related to their preferred water depth. The bubble trauma scores of the experimental fish in TDG supersaturated water significantly increased with exposure time and significantly decreased after recovery in freshwater. The relative and absolute critical swimming speed (Ucrit) of Ctenopharyngodon idella ranged from 10.91 to 12.98 BL/s and 83.3–102.9 cm/s respectively, and there were no significant changes in the Ucrit with increasing TDG supersaturation exposure.